All Days 2008
DOI: 10.2118/112046-ms
|View full text |Cite
|
Sign up to set email alerts
|

Downhole Multiphase Metering In Wells By Means Of Soft-sensing

Abstract: Multiphase flow meters are indispensable tools for achieving optimal operation and control of wells as these meters deliver real-time information about their performance. For example, multiphase flow meters located downhole can improve the production of multilateral and multizone wells by timely allocating the zone where a gas or water cone occurs. However, multiphase meters are either expensive, inaccurate, or cannot be used downhole due to the harsh conditions. An alternative that can be used to overcome the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…This paper follows the soft-sensing framework set out in Leskens et al (2008) and, before that, in Bloemen et al (2004). In Leskens et al (2008), the simultaneous estimation of downhole oil, water and gas flows from downhole pressure and temperature measurements in a unilateral well is considered.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper follows the soft-sensing framework set out in Leskens et al (2008) and, before that, in Bloemen et al (2004). In Leskens et al (2008), the simultaneous estimation of downhole oil, water and gas flows from downhole pressure and temperature measurements in a unilateral well is considered.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative is to use softsensors. Softsensors estimate downhole holdups and flow rates from (relatively) cheap and reliable conventional downhole meters, such as pressure and temperature measurements, and a dynamic multiphase flow model connecting these measurements with the quantities of interest.Soft-sensing has already been investigated before for unilateral wells in Bloemen et al (2004) and Leskens et al (2008). In the second of these references, the simultaneous estimation of downhole oil, water and gas flows from downhole pressure and temperature measurements is considered.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leskens et al [6] considered the simultaneous estimation of downhole oil, water and gas flow rates from downhole pressure and temperature measurements in a single horizontal well using the extended Kalman filter. It has been shown that in case of measurements that are corrupted with noise, obtaining correct estimates is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the Kalman filter has been used for tuning the parameters of two phase flow models (Lorentzen et al, 2003). Leskens et al (2008) considered the simultaneous estimation of downhole oil, water and gas flow rates from downhole pressure and temperature measurements in a single well. This approach has been extended by de to the multilateral well case both for the two-phase (oil and gas) and three-phase (oil, gas and water) cases.…”
Section: Introductionmentioning
confidence: 99%